2003
DOI: 10.1017/s1357729800059051
|View full text |Cite
|
Sign up to set email alerts
|

The ability of the n-alkane technique to estimate intake and diet choice of sheep

Abstract: This study assessed the efficacy of the n-alkane technique to estimate intake and diet composition in animals given single foods or a choice of two. In thefirst experiment intakes of pelleted ryegrassand lucerne, given eitheralone or as a choice, were measured in lambshoused indoors in individual pens. Each of the three feeding treatments was given to 12 lambs at two degrees of maturity (0.30 and 0·45 of estimated mature sizes). The 12 lambs were constituted as three replicates of the two sexes of each of two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…Unfortunately, faecal recovery of short even-chain alkanes is incomplete, increasing as the carbon chain length becomes longer. 5,8,9 In the present study, average faecal recoveries were 77% (SEM 1.7), 81% (SEM 4.6), 101% (SEM 2.6), 92% (SEM 2.8) and 95% (SEM 2.1) for C 24 , C 26 , C 28 , C 30 and C 32 alkanes respectively. Except for C 28 , whose faecal recovery was unexpectedly high, the recovery rates of dosed alkanes in the present study were in agreement with those reported by other authors.…”
Section: Discussionsupporting
confidence: 51%
“…Unfortunately, faecal recovery of short even-chain alkanes is incomplete, increasing as the carbon chain length becomes longer. 5,8,9 In the present study, average faecal recoveries were 77% (SEM 1.7), 81% (SEM 4.6), 101% (SEM 2.6), 92% (SEM 2.8) and 95% (SEM 2.1) for C 24 , C 26 , C 28 , C 30 and C 32 alkanes respectively. Except for C 28 , whose faecal recovery was unexpectedly high, the recovery rates of dosed alkanes in the present study were in agreement with those reported by other authors.…”
Section: Discussionsupporting
confidence: 51%
“…These "fingerprints" have already been explored with success to estimate the proportions of different plant species and/or plant parts in mixtures of ten herbage species (Hoebee et al, 1998) and from faeces of different animal species fed up to five dietary components in sheep (Lewis et al, 2003, Valiente et al, 2003, Ferreira et al, 2006, goats (Brosh et al, 2003, Ferreira et al, 2005, cattle (Brosh et al, 2003;Ferreira et al, in press) and equines (Ferreira et al, in press) in indoor controlled studies.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the accuracy of diet estimates may change according to the n ‐alkanes present in the feed components (as well as with their concentrations) that the animals are eating. The majority of the studies with alkanes have been conducted with sheep and with vegetation where herbaceous species were dominant 11–13. The objective of the present work was to investigate the accuracy of using n ‐alkanes to estimate diet composition of goats when varying the proportions of browse and herb feeds in order to apply this technique to goats grazing mosaics of heather–gorse communities interspersed by patches of grass and clover.…”
Section: Introductionmentioning
confidence: 99%